The resilience of corporate tourism: bleisure, digitalization, and sustainability - Puerta López, María Elena; Pindado Martínez, Julián; González Alvarado, Tania Elena (Mercados y Negocios, 2023)
The study aims to analyze the resilience of corporate tourism in the last three years. Interviews were conducted with industry professionals, and a questionnaire was applied to corporate clients. The results show that adaptation was achieved through short-term planning, bleisure tourism, digitalization, and sustainability. The main conclusion is that resilient companies have changed their line of business, accepted to operate in the short term, and offered more flexibility in pricing.